2017
DOI: 10.4306/pi.2017.14.2.141
|View full text |Cite
|
Sign up to set email alerts
|

The Korean Version of the Schizophrenia Cognition Rating Scale: Reliability and Validity

Abstract: ObjectiveThis study's aim was to develop and standardize a Korean version (SCoRS-K) of the Schizophrenia Cognition Rating Scale (SCoRS), which is used to evaluate the degree of cognitive dysfunction affecting the everyday functioning of people with schizophrenia.MethodsEighty-four schizophrenia patients with stable symptoms who were receiving outpatient treatment and rehabilitation therapy, and 29 demographically matched non-patient controls, participated in the study. Demographic data were collected, and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Complete administration of the SCoRS also involves an interview with an informant (someone in regular contact with the patient). We used the Korean version, SCoRS-K, presented in our previous validation study [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete administration of the SCoRS also involves an interview with an informant (someone in regular contact with the patient). We used the Korean version, SCoRS-K, presented in our previous validation study [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…We used the Korean version, SCoRS-K, presented in our previous validation study. 20 In this study, due to the insufficient number of informant and patient ratings, we used only the interviewer ratings. The interviewer's global rating of the SCoRS was considered the main outcome measure.…”
Section: The Schizophrenia Cognition Rating Scale (Scors)mentioning
confidence: 99%
“…MSCEIT-ME represents to date the only measure that assesses emotional regulation, a subdomain of the emotional processing domain. Italian [173]; Chinese [159]; Malay [159], Japanese [161]. ER-40 [174] Computer administered task that assesses facial emotion recognition ability.…”
Section: Theory Of Mind 6-7 Minutesmentioning
confidence: 99%
“…Moreover, this study revealed a relationship between verbal fluency and employment. A study conducted by Kang et al reported a significant correlation between the Schizophrenia Cognitive Rating Scale and the Social and Occupational Functioning Assessment Scale in patients with schizophrenia [ 42 ]. Furthermore, McGurk et al conducted cognitive function training for patients with severe psychiatric disorders, mainly schizophrenia, and found that the employment rate of the training group was significantly higher than the non-training group after 1 year [ 12 ].…”
Section: Discussionmentioning
confidence: 99%